Carbon status and structural stability of soils from differing land use systems in the Kingdom of Tonga. (6th August 2014) - Manu, V.; Whitbread, A.; Blair, N.; Blair, G.
Abstract Maintenance of soil carbon stocks is vital for the environment at large and for maintenance of soil chemical, physical and biological fertility. Tonga represents a country in agricultural transition from subsistence to commercial production and whilst this is good for the national economy the impact on soil resources is less clear. The major cropped soils, fallow vegetation types and forest systems of Tonga were identified in each island group and samples of representative soils (0.15 m depth) from each land use unit were taken. Total carbon (CT) and δ13C were measured and labile carbon (CL) determined by oxidation with 333 mm KMnO4. These data were used to determine the carbon management index (CMI) and the proportion of carbon from C4 species in the CT pool. Relative to primary forest, the soil CT and CL generally declined with changes in vegetation and more intense mechanical tillage. The contribution of C4 plants to soil C increased with intensity of mechanical tillage and the prevalence of C4 guinea grass (Panicum maximum Jacquin) fallow. The changes in soil C were reflected in the CMI, and CL was a more sensitive indicator of change than CT. These data indicates that all land use systems have experienced a large net loss of soil C relative to the forest systems. Soil mean weight diameter (MWD) decreased significantly with increased intensity of mechanical tillage and to a lesser extent with the intensity and length of cropping. The relationship between soil MWD and soil C was similar with soil CT and CL. Grass fallow was as effective as permanent vegetation systems in improving soil MWD and lowering the micro‐aggregate (<125 μm) fraction.